Lazer, juventude e escola: um estudo de revisão sistemática da literatura - Santos, Carlos Israel Rodrigues dos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present study aimed to investigate the field of academic-scientific production on the theme of leisure and youth in interface with the school context through a systematic review of the literature. We seek to identify and characterize such studies, as well as analyze the objectives and conclusions of the studies identified with this theme. The analysis made it possible to identify that leisure is a component of youth cultures and the systematization of this knowledge supports possibilities of experiencing it in the school environment, exploring cultural contents, contributing significantly to the critical enjoyment by young people outside of school. We consider that the studies carried out unveiled possibilities and problematized the effectiveness of education for and through leisure, because while they demonstrated that it is essential knowledge for the reflective and critical training of students in/to experience leisure, it is still a neglected content in the school curriculum, especially in high school, being necessary and urgent to implement educational policies that rethink the place of discredit that leisure has occupied in the school institution

O presente estudo se propôs a investigar o campo da produção acadêmico-científica na temática do lazer e juventudes em interface com o contexto escolar através da revisão sistemática da literatura. Buscamos identificar e caracterizar tais estudos, bem como, analisar os objetivos e conclusões dos estudos identificados com esta temática. A análise permitiu identificar que o lazer é um componente das culturas juvenis e a sistematização desse conhecimento embasa possibilidades de vivenciá-lo no âmbito escolar, explorando os conteúdos culturais, contribuindo de modo significativo para fruição crítica pelos/as jovens fora da escola. Consideramos que os estudos realizados desvelaram possibilidades e problematizaram a efetivação da educação para e pelo lazer, pois ao passo que demonstraram que é um conhecimento essencial para formação reflexiva e crítica dos/as estudantes na/para vivência do lazer, ainda é um conteúdo preterido no currículo escolar, especialmente no ensino médio, sendo necessário e urgente implementar políticas educacionais que repensem o lugar de desprestígio que o lazer tem ocupado na instituição escolar
Leisure, youth and school: a systematic literature review study
Keywords: Leisure; Youth; Physical education; Lazer; Juventude; Escolas; Revisão; Educação física